Analysis on the progress of all-optical network standardization and technology development - Rui TANG; Geng ZHANG; Bingbing WU; Wenyu ZHAO; Haiyi ZHANG (Dianxin kexue)
All-optical network has been considered as the ultimate goal of the optical communication network.With the development of liquid crystal and MEMS technologies and the maturity of configurable optical devices such as WSS,all-optical network has once again become the focus of research and application.Based on the technical status and system architecture of the all-optical network,the technical problems to be solved in the all-optical network were discussed,the latest developments in standardization research were sorted out,the typical problems existing in the all-optical network standardization were further analyzed,and its future developments were finally forecasted.